DIFFICULTY ANALYSIS OF DEVELOPMENT OF WONDERSHARE QUIZ CREATOR AS A MEDIA FOR EVALUATION OF CHEMICAL LEARNING BASED ON HOTS - Irfandi Irfandi; Rosa Murwindra (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2022)
The purpose of this study was to analyze the difficulties faced in developing wondershare quiz creator as an evaluation medium for HOTS-based chemistry learning on salt hydrolysis material. The approach used in this research is a case study. Based on the results of the data, the difficulties experienced in developing the wondershare quiz creator as an evaluation medium for chemistry learning were obtained, namely: (1) difficulties in finding questions that were in accordance with 21st century learning, because 21st century learning requires evaluation based on High Orther Thinking Skills (HOTS) (2) Lack of cost, time, supporting facilities in media development; (3) Lack of creativity in developing interactive evaluation media.